Pulse regulation effect and nonlinear dynamic model of polyurethane waveform generators - Yang, Guanxia; Wu, Haijun; Dong, Heng; Yang, Yekai; Huang, Fenglei (International journal of impact engineering, 2023)
•The pulse regulation effect of the polyurethane waveform generator is investigated experimentally.•The impact process of metal/PWG multi-layer composite projectiles is systematically analyzed.•A nonlinear visco-hyperelastic dynamic model is developed for the PWG.•The impact pulses of direct impact tests are predicted based on the dynamic model of PWG. Using projectile impact to simulate blast/shock loading is an effective laboratory-scale loading method that has attracted great attention. As a part of the projectile, the waveform generator plays a significant role in regulating the impact pulse. In order to investigate the pulse regulation effect of polyurethane waveform generators (PWGs) and establish its dynamic model, direct impact tests of metal/PWG multi-layer composite projectiles (MCPs) with different PWG configurations were performed. The effects of PWG hardness, impact velocity, and PWG geometric parameters on the characteristic parameters of the impact pulse were investigated. The results revealed that, compared with the metal projectiles, the peak pressure of the metal/PWG MCPs was reduced by 95.00%, and the peak specific impulse was increased by 73.86%. Correlation analysis demonstrated that the peak pressure decreased exponentially with the increase of the PWG DH (the product of diameter and thickness), while the duration and the peak specific impulse showed 2-order and 3-order nonlinear increasing trend, respectively. After establishing a quantitative relationship between the characteristic parameters of the impact pulse and the impact velocity, it was found that with the increase of the impact velocity, the peak pressure and peak specific impulse exhibited a 3-order nonlinear rapid growth and linear increasing trend, respectively, while the pulse duration exhibited a 2-order nonlinear decreasing trend. In addition, a nonlinear dynamic model was established to describe the large deformation dynamic characteristics of PWGs. The PWG geometric parameters and the impact velocities were incorporated into the model through the quasi-static compression test of PWGs and direct impact tests of the projectiles. Based on the nonlinear dynamic model, the impact pulses of direct impact tests were predicted, and agreed well with the experimental results. This verified the capability of the proposed model to describe the dynamic characteristics of PWGs. The impact pulse prediction model established in this study provides a basis for the dimension design of PWGs and the setting of the impact velocity in blast/shock simulation tests.